2023
DOI: 10.1093/jimb/kuad005
|View full text |Cite
|
Sign up to set email alerts
|

Cytochromes P450 involved in bacterial RiPP biosyntheses

Abstract: Ribosomally synthesized and post-translationally modified peptides (RiPPs) are a large class of secondary metabolites that have garnered scientific attention due to their complex scaffolds with potential roles in medicine, agriculture, and chemical ecology. RiPPs derive from the cleavage of ribosomally-synthesized proteins and the additional modifications, catalyzed by various enzymes to alter the peptide backbone or side chains. Of these enzymes, cytochromes P450 are a superfamily of heme-thiolate proteins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…12,13 More recently, ribosomal biosynthesis pathways (Ribosomally synthesized and post-translationally modified peptides (RiPPs)) involving P450 cross-linking reactions have been widely reported and investigated, showing high levels of diversity in the reactions catalyzed and the substrates accepted by this intriguing group of P450s. 14 While many of these new classes of P450s utilize large leader sequences relative to their smaller core peptides, the biarylitides 15 (and related myxarylins) 16 are remarkably atom efficient in their use of a two amino acid leader appended to a three amino acid core peptide. Biochemical characterization has shown that the biarylitide P450s possess the ability to generate alternate (C− C, C−N) cross-links within their Tyr-Xaa-His cores (where Xaa can be highly varied) and furthermore that these enzymes can also tolerate a range of modifications within the cross-link and even the replacement of the terminal His residue with Trp.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 More recently, ribosomal biosynthesis pathways (Ribosomally synthesized and post-translationally modified peptides (RiPPs)) involving P450 cross-linking reactions have been widely reported and investigated, showing high levels of diversity in the reactions catalyzed and the substrates accepted by this intriguing group of P450s. 14 While many of these new classes of P450s utilize large leader sequences relative to their smaller core peptides, the biarylitides 15 (and related myxarylins) 16 are remarkably atom efficient in their use of a two amino acid leader appended to a three amino acid core peptide. Biochemical characterization has shown that the biarylitide P450s possess the ability to generate alternate (C− C, C−N) cross-links within their Tyr-Xaa-His cores (where Xaa can be highly varied) and furthermore that these enzymes can also tolerate a range of modifications within the cross-link and even the replacement of the terminal His residue with Trp.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This is particularly notable in the biosynthesis of several important classes of nonribosomal peptides (NRPs), including the glycopeptide antibiotics (GPAs, such as vancomycin, teicoplanin and corbamycin) and arylomycin . While P450s from NRP pathways have been characterized, and in the case of GPAs also in complex with their essential recruitment domains, , none of these P450s have been in a substrate bound form, making an assessment of the mechanism utilized and the substrate binding mode employed by these enzymes elusive. , More recently, ribosomal biosynthesis pathways (Ribosomally synthesized and post-translationally modified peptides (RiPPs)) involving P450 cross-linking reactions have been widely reported and investigated, showing high levels of diversity in the reactions catalyzed and the substrates accepted by this intriguing group of P450s . While many of these new classes of P450s utilize large leader sequences relative to their smaller core peptides, the biarylitides (and related myxarylins) are remarkably atom efficient in their use of a two amino acid leader appended to a three amino acid core peptide.…”
Section: Introductionmentioning
confidence: 99%
“…One Nocardia BGC contained a member of protein family PF00067, 12 a predicted cytochrome P450 protein. While P450-encoding genes are relatively rare in bacterial RiPP BGCs, 13 they have yet to be reported in a lasso peptide BGC. Since RiPP-associated P450 proteins perform versatile and complex oxidative transformations, 13,14 we envisioned such BGCs would yield a new type of lasso peptide.…”
Section: Introductionmentioning
confidence: 99%
“…While P450-encoding genes are relatively rare in bacterial RiPP BGCs, 13 they have yet to be reported in a lasso peptide BGC. Since RiPP-associated P450 proteins perform versatile and complex oxidative transformations, 13,14 we envisioned such BGCs would yield a new type of lasso peptide. Thus, we characterized the products of this pathway, termed the nocapeptins, given the origin was Nocardia terpenica (taxonomic order: Corynebacteriales).…”
Section: Introductionmentioning
confidence: 99%
“…While P450s impress by their tremendously functional versatility that is involved in the biosynthesis of abundant secondary metabolites including polyketides (PKs), nonribosomal peptide (NRPs), cyclodipeptides (CDPs), and terpenes (Figure ), the involvement of P450s in the biosynthesis of RiPPs is comparatively limited and few reviews have been summarized for this field to my knowledge (Table ). While this Review was under preparation, Kunakom et al published an excellent review about P450s involved in bacterial RiPP biosynthesis, with emphases on the distribution of P450s in bacterial genomes and the biosyntheses of atropitides, biarylitides, cittlins, as well as nocathiacin that harbors rich P450s . Herein, this Review provides a more comprehensive description of all the P450s with functionalities in the PTMs of RiPPs to date according to different classifications (Table ), including P450s involved in some eukaryotic RiPP biosyntheses.…”
Section: Introductionmentioning
confidence: 99%